Estimation of the carbon footprint of arthroscopic rotator cuff repair in France. Issue 3 (30th March 2022) - Rougereau, Gregoire; Chatelain, Léonard; Conso, Christel; Zadegan, Frédéric
Objectives: Global warming is certainly one of the greatest challenges of the century. The objective of this work is to estimate the carbon footprint of arthroscopic rotator cuff repair, and to evaluate the positive impact of the following actions: ambulatory surgery, performed under loco-regional anesthesia, and filtration of surgical fluids. Methods: The assessment protocol was compliant with the Greenhouse Gas Protocol, which has three components: 1/ use of volatile anesthetic agents; 2/ electric consumption related to the procedure (heating and air conditioning, ventilation, computer); 3/ related to patient and staff travel, implant delivery and waste management. The study covered the period from November 2020 to April 2021, and included any patient undergoing arthroscopic shoulder replacement surgery. Three actions aimed at improving the carbon footprint were taken: ambulatory surgery, performed under local anesthesia, and filtration of surgical fluids by Neptune® (Stryker). To examine the effectiveness, each patient included during the review period was matched to a patient who underwent surgery during 2018 before the implementation of this protocol. Results: Finally, 26 patients were included. The carbon footprint of arthroscopic rotator cuff repair was estimated at 260.5 +/- 35.03 kgCO2 eq. The main impacts could be attributed to single-use equipment (53.5%), restocking anchors (27.2%), contaminated waste incineration (5.9%), the sterilization process (5.4%), and traveling by the patient (4.1%). Setting up ambulatory surgery without the use of anesthetic gases and a water purifier reduced emissions by 25.9 +/- 2.5 kgCO2 eq (9.3%) per procedure. Conclusion: The carbon footprint of arthroscopic rotary cuff repair corresponds to a bit more than 60 km traveled in a car. The main factor that should be addressed is the impact related to single-use materials and inventory management.